Análisis del efecto causado por la aplicación de la ley para la justicia laboral (pago de pensiones de los jubilados del Instituto Ecuatoriano de Seguridad Social), en las universidades del D.M.Q. - Salazar Lalvay, Carla Lizbeth (2018)
The objective of the present research is to analyze the effect that occurs with the implementation of the law for the labour courts in the ancient and future retirees of the Ecuadorian Institute of Social Security with regard to the payment of the pension by retirement and its impact on the universities being public and private of the Metropolitan District of the city of Quito. Through research conducted at 12 universities within the Metropolitan District of Quito, was allowed to determine that the effect of the application of the law for the Labour Court applied to the payment of retirement, is unfavorable for the institutions educational level, where an increase is projected in the payment of pensions Jubilee for employers, in addition to the Ecuadorian Social Security Institute conceived strong problems to pay for pensions for all pensioners members and volunteers, without funding from the State, this is due to that the Ecuadorian Social Security Institute has some difficulty in payment of these pensions entirely. This study was carried out due to the problems of the universities of the district Metropolitan of Quito, the payment of pension retirement; In addition to study is the effect on the institution of Social Security to make these disbursements; should be noted that this article will be updated annually, this by means of pictures, stats, graphs and definitions to facilitate more research information on the subject of payment of pension, retirement, and social security.